DESIGN OF INFORMATION MEDIA REGISTRATION FLOW FOR NEW STUDENT ACCEPTANCE OF ICHSAN GORONTALO UNIVERSITY THROUGH INFOGRAPHICS: DESIGN OF INFORMATION MEDIA REGISTRATION FLOW FOR NEW STUDENT ACCEPTANCE OF ICHSAN GORONTALO UNIVERSITY THROUGH INFOGRAPHICS - Risti Puspita Sari Hunowu; Apsari Dj.Hasan; Samsuddin, Samsuddin; Muhammad fahri labanga (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
Ichsan Gorontalo University is one of the favorite private universities in Gorontalo province. Every year there are hundreds of registrants from various regions. The aim of the research is to provide information on registration procedures for prospective new students in a way that is interesting and easy to understand. The lack of social media for prospective new students regarding the steps that must be taken to be officially registered as students at Ichsan University Gorontalo often causes applicants to find it difficult to register. This research uses interview methods with New Student Admissions (PMB) employees, observations of prospective applicants and literature studies on books, journals and research-related literature as reference material. In making this infographic, you use a combination of various media, such as writing and images which are packaged using Adobe Illustrator software to produce a poster or banner. The results of this research are registration flow infographics in the form of posters and banners which can be disseminated online via the New Student Admissions (PMB) website and social media at Ichsan Gorontalo University and can be displayed on the Ichsan Gorontalo University campus.